2022
DOI: 10.1177/19485506221141661
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Updated Implicit Evaluations and the Trust Game

Abstract: Recent work has shown that people can update their implicit evaluations based on facial trustworthiness. However, do these updated implicit evaluations map onto subsequent decisions? We examined whether implicit evaluations based on faces but updated in light of new behavioral evidence uniquely predict responses in the trust game. Across six studies ( N = 2,059), we measured participants’ initial implicit evaluations of a target based on the target’s face and then their updated implicit evaluations based on ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…If a self-reported outcome is conceptually overlapping with a self-reported evaluation, there may be little room for an implicit evaluation to predict the outcome. Recently, Shen and colleagues (2022) showed that implicit evaluations of an individual did not uniquely predict self-reported money-allocating decisions. Although speculative, this might be because self-reported evaluations of an individual are highly conceptually redundant with self-reported trust decisions, and past work has indeed argued for the close overlap between positive evaluations and trust (Fiske et al, 2007).…”
mentioning
confidence: 99%
“…If a self-reported outcome is conceptually overlapping with a self-reported evaluation, there may be little room for an implicit evaluation to predict the outcome. Recently, Shen and colleagues (2022) showed that implicit evaluations of an individual did not uniquely predict self-reported money-allocating decisions. Although speculative, this might be because self-reported evaluations of an individual are highly conceptually redundant with self-reported trust decisions, and past work has indeed argued for the close overlap between positive evaluations and trust (Fiske et al, 2007).…”
mentioning
confidence: 99%